THE USE OF WEB 2.0 TOOLS IN LOCAL GOVERNMENT: AN EMPIRICAL STUDY IN TURKISH MUNICIPALITIES - Melih ENGİN (Fırat University, 2019)
The increasing popularity of personal computers and internet use by the citizens made it necessary for the governments to use the same platforms. The objective of the study is to determine the usage of web 2.0 tools in local governments. The study presented the Web 2.0 tools in general and after, the explanation for the use of the administrative sense is done. Later on, the findings of web 2.0 tools for the information, interaction and transaction based usage of the municipalities of 81 provinces in Turkey was obtained. The Results demonstrated that the usage of web 2.0 technologies by the municipalities in Turkey was at a very low level and concentrated on a few web 2.0 technologies. Municipal governments focus on providing information while using web 2.0 tools and the use of web 2.0 technologies to provide efficient services and participation remain in the background.